Structure–function analysis for the hydroxylation of Δ4 C21‐steroids by the myxobacterial CYP260B1. Issue 12 (3rd June 2016) - Salamanca‐Pinzon, Sandra Giovanna; Khatri, Yogan; Carius, Yvonne; Keller, Lena; Müller, Rolf; Lancaster, C. Roy D.; Bernhardt, Rita
Abstract : Myxobacterial CYP260B1 from Sorangium cellulosum was heterologously expressed in Escherichia coli and purified. The in vitro conversion of a small focused substrate library comprised of Δ4 C21‐steroids and steroidal drugs using surrogate bovine redox partners shows that CYP260B1 is a novel steroid hydroxylase. CYP260B1 performs the regio‐ and stereoselective hydroxylation of the glucocorticoid cortodoxone (RSS) to produce 6β‐OH‐RSS. The substrate‐free crystal structure of CYP260B1 (PDB5HIW ) was resolved. Docking of the tested ligands into the crystal structure suggested that the C17 hydroxy moiety and the presence of either a keto or a hydroxy group at C11 determine the selectivity of hydroxylation. Abstract : CYP260B1 converts Δ4 C21‐steroids and steroidal drugs. CYP260B1 catalyzes a regio‐ and stereoselective hydroxylation of the glucocorticoid cortodoxone (RSS) to 6β‐OH‐RSS. The ligand‐free crystal structure of CYP260B1 was solved. Docking of RSS into the crystal structure of CYP260B1 showed a single pose with C6 close to heme‐iron. CYP260B1 converts steroidal drugs. The optimized E. coli ‐based whole‐cell biocatalyst developed in this study has the potential to screen other pharmaceutically important steroids and steroidal drugs for the generation of steroidal and drug derivatives.